Modelling approach to predict the fire-related heat transfer in porous gypsum based on multi-phase simulations including water vapour transport, phase change and radiative heat transfer. (April 2022) - Prieler, Rene; Langbauer, Raphael; Gerhardter, Hannes; Kitzmüller, Peter; Thumser, Stefan; Schwabegger, Günther; Hochenauer, Christoph
Abstract: The heat transfer in gypsum exposed to fire is significantly affected by heat conduction, mass transfer and condensation/evaporation effects of water vapour in the porous structure. In the past, numerical models to predict the heat transfer in gypsum were mainly limited to heat conduction and mass transfer of water vapour in thin gypsum boards used in wall assemblies. Thus, in the present study a multi-phase approach is proposed to predict the heat transfer within gypsum under fire exposure including conduction, mass transfer and condensation/evaporation. The consideration of water vapour transport and its condensation in the porous structure was leading to a good prediction of the heating process of gypsum up to approx. 100 °C. Furthermore, the calculated temperatures above 100 °C were adequate up to 2 cm from the fire side. However, at a higher distance from the fire the additional implementation of a thermal radiation model was crucial to improve the heat transfer in gypsum. Including the thermal radiation, the proposed numerical model is able to calculate the temperatures in the gypsum blocks in close accordance to the measurement. Highlights: Fire resistance test of gypsum and measurement of the temperature profile. Lee model to predict evaporation/condensation of water in porous gypsum. Multi-phase approach for the water vapour transport through gypsum in fire tests. Thermal radiation modelling in porous gypsum with discrete ordinates model (DOM). Porosity-corrected DO modelling was successfully used for radiation in gypsum.